Physio-morphological characters, yield, fruit quality and leaf nutrient status of filler plant guava (Psidium guajava) as influenced by mango (Mangifera indica) based intercropping systems - SWAIN, S C; DORA, D K; PADHI, S K; SINGH, RANVIR (The Indian Journal of Agricultural Sciences, 2026)
A mango based intercropping experiment comprising of nine treatments such as mango ginger (Curcuma amada Roxb.), turmeric (Curcuma longa L.), tomato (Solanum lycopersicum L.), cowpea (Vigna unguiculata (L.) Walp.), frenchbean (Phaseolus vulgaris L.), ragi (Eleusine coracana Gaertn.), niger (Guizotia abyssinica Cass.), upland paddy(Oryza sativa L.) and control (without intercrop) along with filler crop guava (Psidium guajava L.) was laid out in Randomized Block Design with three replications to assess the effect of various intercrops on the performance of filler crop guava in the rainfed uplands of Odisha. The results of the study revealed that the growth of guava plants has been appreciably influenced by the intercropping systems tried in the study which was evident from the incremental growth measured in terms of height, girth, and canopy area of the concerned trees. The fruit setting percentage, fruit retention, fruit weight and fruit yield of guava was recorded highest in mango + guava +cowpea intercropping system closely followed by mango + guava + frenchbean system. The leaf analysis result after completion of the investigation indicated that the N, P and K content of guava leaf were found to be maximum under the above mentioned treatment. The quality parameters such as TSS and acidity were not significantly affected by intercropping during both the years of study.